When Fast Growing Economies Slow Down: International Evidence and Implications for the People's Republic of China - Barry Eichengreen; Donghyun Park; Kwanho Shin (Asian Development Bank (ADB), 2011)
This paper analyzes international historical evidence and finds that economic growth slows down when per capita income reaches USdollar17,000.
hdl:11540/2021
Keywords: 330; Development Economics; Regional Economic Development; Economic Impact; Asian Development Bank; Development; Economies in transition; Wirtschaftswachstum; Stagnation; Welt; China